Review on the Physical Fitness of Sports Performance: Comparative study on physical fitness levels and the impact of exercise training among urban college students of different weight categories (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this paper the physical fitness level among normal weight and hefty urban college understudies. The subsequent point was to explore the impact of exercise training on some physical fitness factors between these understudies. Thirty stationary urban clinical understudies from Medical Sciences University of Tehran relegated on two separate gatherings of normal weight (n=15, BMI=21.58±1.13) or corpulent (n=15, BMI=28.22 ±5.84).Anthropometric measurements included were tallness, weight, age and Body Mass Index (BMI). Provincial fitness tests (One mile run for assurance of cardiovascular perseverance, Bench and leg press for assurance of upper and lower appendage solid quality, Sit-up and push-up for assurance of midsection and shoulder strong continuance and sit and arrive at test for assurance of adaptability. All physical fitness tests were surveyed when exercise training program.